Moderate Grazing Increases Water Use Efficiency for Environmental Health in Alpine Meadows of the Tibetan Plateau - Wang, Yunying; Pei, Weiwei; Cao, Guangmin; Guo, Xiaowei; Zhou, Huakun; Du, Yangong (Frontiers in Ecology and Evolution, 2021)
Water use efficiency is an important indicator of drought tolerance of plants. The response was still unclear of water use efficiency to different grazing intensity and its adaptive mechanisms in alpine meadow. Here, we analyzed water use efficiency of plant dominant species, coexisting species and functional group level plants to grazing intensity by δ13C index in alpine meadow. Furthermore, this study revealed the driven factors of water use efficiency combined available nitrogen, soil bulk density, soil organic carbon, soil water content and evapotranspiration. Grazing increased plants δ13C by 3.37%. Moderate grazing significantly increased the δ13C of Gramineae by 4.84% (P<0.05), and increased δ13C of Cyperaceae, Leguminosae, and Forb by 3.45%, 0.81%, and 1.40% respectively. Some dominant species and coexisting species have the highest δ13C value under moderate grazing. This study indicated that moderate grazing significantly improved the water use efficiency of alpine meadows. Path analysis resulted showed that the water use efficiency was negatively correlated with evapotranspiration (P<0.05), soil water content, soil organic carbon, and soil bulk density. It was positively correlated with available nitrogen. Our study provides new insights that moderate grazing help to increase water use efficiency in alpine meadows. In addition, evapotranspiration may be the main driving factor affecting the water use efficiency of alpine meadow.